The Use Of Scanning Method To Improve Students’ Reading Comprehension - Zainal Arifin; Yon A E; Lenny Solo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aimed at improving the students’ reading comprehension by using scanning method in the process of reading teaching and learning at tenth grader of SMK Teknikom Bekasi. This research used Classroom Action Research (CAR) which in conducted to solve the student’s problem in English reading. The Classroom Action Research (CAR) was done based on Kemmis and Mc Taggart design. This research consisted of two cycles in which cycle consists of planning, action, observation and reflection. The data were gathered through qualitative and quantitative data. The qualitative data were gained by analyzing the interview and observation result. Then, the quantitative data were obtained from the student’s score of pre-test and post-test. The researcher enhanced the trustworthiness of the data and the subjectivity by using the two forms of triangulation: time and researcher triangulation. The result of two cycles showed that the use of the scanning method could improve the students’ reading ability. The students got improvements ability in find the word quickly. In the class X TKJ C which 33 student all student get score above KKM and get result of the average score of the students is 82,61. Moreover, through the scanning method, the students were motivated to be active in classroom activities. They were actively involved in the process of teaching and learning. This condition stimulated the students to work based on their own actual capability. Thus, the students got more experiences and improved their achievement.